2016
DOI: 10.1159/000444870
|View full text |Cite
|
Sign up to set email alerts
|

A Cytogenomic Approach in a Case of Syndromic XY Gonadal Dysgenesis

Abstract: This is the first molecular characterization of a female XY patient with an Xp duplication due to an X;22 translocation. Array CGH detected a copy number gain of ∼36 Mb in the Xp22.33p21.1 region involving 150 genes. Clinical and molecular studies described in the literature have suggested DAX1 duplication as the major cause responsible for a sex reversal phenotype. Additionally, the interaction between genes and their possible role in clinical features are presented to support the discussion on genotype-pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2). The number of genes contained in these chromosomal segments varied significantly [Barbaro et al, 2007;Ledig et al, 2010;White et al, 2011;Jaillard et al, 2015;Dong et al, 2016;Simioni et al, 2016]; however, NR0B1 and MAGEB1, MAGEB2, MAGEB3, and MAGEB4 were identified in the chromosomal segments of all these patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…2). The number of genes contained in these chromosomal segments varied significantly [Barbaro et al, 2007;Ledig et al, 2010;White et al, 2011;Jaillard et al, 2015;Dong et al, 2016;Simioni et al, 2016]; however, NR0B1 and MAGEB1, MAGEB2, MAGEB3, and MAGEB4 were identified in the chromosomal segments of all these patients.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to these molecular cytogenetic approaches, array-CGH and SNP-array are able to detect submicroscopic CNVs across the whole genome and identify rearrangements of known gonadal genes or their regulatory sequences [Smyk et al, 2007;Kon and Fukami, 2015;Dangle et al, 2017], as well as new genes involved in abnormal gonadal development [Ledig et al, 2010;Igarashi Norling et al, 2013]. Thus, their use has meaningfully contributed toward elucidating the diagnosis of syndromic and non-syndromic 46,XY GD [Barbaro et al, 2007;Ledig et al, 2010;White et al, 2011;Norling et al, 2013;Jaillard et al, 2015;Simioni et al, 2016].…”
Section: Discussionmentioning
confidence: 99%